2018
DOI: 10.1585/pfr.13.1205001
|View full text |Cite
|
Sign up to set email alerts
|

Pulsation Effects of Incident Ion Energy on W Fuzz Growth

Abstract: Fuzzy nanostructure growth occurs on tungsten (W) surfaces by the exposure to helium (He) plasmas. We investigated pulsation effect in the incident energy of He ions on W fuzz growth. It is shown that He irradiation contributes to the growth of fuzzy layer even if the incident ion energy was less than the threshold energy of 20 -30 eV. When the duty cycle of the pulse was 1 -10 %, 7 -8 eV He ion irradiation have contributed to the fuzz growth in addition to high (> 60 eV) energy ion irradiation, and the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was revealed from laser heating experiments that an enhancement of fuzz growth occurred with transient temperature increases [14]. An ion energy pulsation experiments demonstrated that a low energy irradiation less than 20 eV also contributed to the fuzz growth if pulses existed [15]. Another issue could be the effect of re-deposition, which would be important for various issues including deuterium accumulation [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed from laser heating experiments that an enhancement of fuzz growth occurred with transient temperature increases [14]. An ion energy pulsation experiments demonstrated that a low energy irradiation less than 20 eV also contributed to the fuzz growth if pulses existed [15]. Another issue could be the effect of re-deposition, which would be important for various issues including deuterium accumulation [16].…”
Section: Introductionmentioning
confidence: 99%
“…The incident He ion energy near the strike point of ITER divertor would be lower than the threshold (∼20 eV) for fuzz formation . However, several recent experiments conducted to investigate transient effects on a W surface have revealed that fuzz growth could be accelerated by adding pulsation to the heat load or incident ion energy . Low‐energy He ions, whose incident energy is lower than 10 eV, are especially likely to contribute to the further growth of fuzz when combined with cyclic precipitation of high‐energy ions .…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent experiments conducted to investigate transient effects on a W surface have revealed that fuzz growth could be accelerated by adding pulsation to the heat load or incident ion energy . Low‐energy He ions, whose incident energy is lower than 10 eV, are especially likely to contribute to the further growth of fuzz when combined with cyclic precipitation of high‐energy ions . As the fuzz formation would lead to significant thermal and electrical property changes, these morphology changes should be regarded as an important factor when evaluating the erosion properties of divertor plates …”
Section: Introductionmentioning
confidence: 99%